FTO polymorphisms are associated with adult body mass index (BMI) and colorectal adenomas in African-Americans - Nock, Nora L. (Oxford University Press, 2011)
Obesity is a known risk factor for colon cancer and higher body mass index (BMI) has been associated with colorectal adenomas, which are precursor lesions to most colorectal cancers. Polymorphisms in the fat-mass and obesity-associated (FTO) gene have been associated with BMI and larger effects in older versus younger children have been reported. However, no studies have examined associations between FTO polymorphisms, BMI throughout adulthood and colorectal adenomas. Therefore, we evaluated associations between FTO polymorphisms (rs1421085, rs17817449, rs8050136, rs9939609, rs8044769), adult BMI (at recruitment, 50s, 40s, 30s, 20s age decades) and colorectal adenomas in 759 Caucasians and 469 African-Americans. We found that the highest versus the lowest BMI tertile at recruitment [odds ratio (OR) = 1.82; 95% confidence interval (CI): 1.07–2.16] and in the 30s (OR = 1.50; 95% CI: 1.04–2.15) was associated with higher adenoma risk. Stratification by ethnicity revealed that these associations only remained significant in Caucasians. We found that, in Caucasians, having two versus no copies of the variant allele in rs17817449, rs8050136 and rs9939609, which are all in strong linkage disequilibrium, was associated with higher BMI in the 30s and 40s but none of the polymorphisms were associated with adenomas. In African-Americans, having one or two copies of the variant in rs17817449 (OR = 0.61; 95% CI: 0.39–0.95) and rs8050136 (OR = 0.59; 95% CI: 0.38–0.93) was associated with colorectal adenomas and, having two variant copies in rs17817449 and rs8050136 was associated with higher BMI at recruitment and in the 40s, respectively. Our results are consistent with prior studies and show for the first time that FTO polymorphisms are associated with colorectal adenomas in African-Americans.